Detection of Driver and Resistance Mutations in Leptomeningeal Metastases of NSCLC by Next-Generation Sequencing of Cerebrospinal Fluid Circulating Tumor Cells - Jiang, Ben-Yuan; Li, Yang-Si; Guo, Wei-Bang; Zhang, Xu-Chao; Chen, Zhi-Hong; Su, Jian; Zhong, Wen-Zhao; Yang, Xue-Ning; Yang, Jin-Ji; Shao, Yang; Huang, Biao; Liu, Yan-Hui; et al. (Clinical cancer research, 2017)
Purpose: Leptomeningeal metastases are more common in non–small cell lung cancer (NSCLC) with EGFR mutations. The diagnosis is difficult by traditional imaging only, and leads to poor understanding of resistance mechanisms of leptomeningeal metastases. Experimental Design: We compared the CellSearch Assay, the Thinprep cytologic test (TCT), and brain magnetic resonance imaging (MRI) in 21 NSCLC patients with suspected leptomeningeal metastases. Next-generation sequencing that included 416 cancer-associated genes was also performed on cerebrospinal fluid circulating tumor cells (CSFCTC) of 19 patients. Results: Twenty-one patients were diagnosed with leptomeningeal metastases, and CSFCTCs were captured by CellSearch in 20 patients (median, 969 CSFCTCs/7.5 mL; range, 27–14,888). CellSearch had a sensitivity of 95.2% for leptomeningeal metastases diagnosis, which was higher than that of TCT (12/21, 57.1%), MRI (10/21, 47.6%), and MRI plus TCT (19/21, 90.5%), respectively. CTCs were found only in 5 of 14 patients (median, 2 CTCs/7.5 mL; range, 2–4), which was a much lower ratio than CSFCTCs. Genetic profiles of CSFCTCs were highly concordant with molecular mutations identified in the primary tumor (17/19, 89.5%). The resistance gene EGFR T790M was detected in 7 of 9 patients with extracranial lesions, but was detected in only 1 of 14 CSFCTC samples. Other potential resistant mutations, such as MET amplification and ERBB2 mutation, were also identified in CSFCTCs. Conclusions: CSFCTCs captured by CellSearch may be a more sensitive and effective way to diagnose leptomeningeal metastases, and may serve as a liquid biopsy medium for gene profiles in NSCLC patients with leptomeningeal metastases. Clin Cancer Res; 23(18); 5480–8. ©2017 AACR.